Suspended GaN beams and membranes on Si as a platform for waveguide-based THz applications. (11th July 2018) - Krause, S; Desmaris, V; Pavolotsky, A; Meledin, D; Belitsky, V
Abstract: We demonstrate the suitability of employing suspended GaN beams on a Π-shaped Si frame for waveguide-based cryogenic THz components and systems. This concept addresses major challenges and provides eased device handling, cryogenic operation, micron-alignment possibilities, high integratability and allows the electrical contacting by using bonding wires. In particular, a balanced hot electron bolometer (HEB) mixer was implemented for frequencies at 1.3 THz with state-of-the-art IF performance, which combines micro-machined all-metal waveguide components in conjunction with a suspended GaN beam. In addition, in order to accomplish a proper design of active or passive components, the accurate knowledge of the effective dielectric constant at THz frequencies is crucial when such membranes are employed. Thus, a direct measurement method based on a resonance structure and an S-parameter measurement between 1 THz and 1.5 THz is also presented.